Bacterial community in homemade kimchi and probiotic characterization of Lactiplantibacillus plantarum HQ04 - Zhao, Wei; Chen, Meilin; Zhang, Yixuan; Fan, Yiping; Zhao, Pinyao; Zhou, Ling; Ouyang, Weimin; Wang, Jie (Frontiers in Microbiology, 2025)
Homemade fermented kimchi is rich in microbial communities and is regarded as an important source of probiotics. In this study, the bacterial community diversity of 40 kimchi samples from Yibin City, China, was analyzed using high-throughput sequencing of 16S rRNA gene. Then, Lactiplantibacillus plantarum (L. plantarum) strains were isolated from the kimchi samples and characterized for their probiotic properties. The strain with the most favorable probiotic traits was further analyzed to identify its genetic characteristics through whole genome sequencing. The results showed that Firmicutes (57.9%) and Proteobacteria (36.3%) were the dominant phyla, whereas Levilactobacillus (19.2%) and Lactiplantibacillus (12.2%) were the most abundant genera. Alpha- and beta-diversity analyses indicated that each kimchi sample comprised an independent microbial ecosystem. A total of 11 L. plantarum strains were isolated, among which strain HQ04 demonstrated superior probiotic properties, such as high tolerance to acid and bile salts, gamma-aminobutyric acid (GABA) production, strong autoaggregation and coaggregation abilities, and potent antibacterial activity. Whole genome sequencing identified five secondary metabolite gene clusters in the HQ04 genome. Additionally, a class II bacteriocin gene cluster encoding Bacteriocin IIc, Enterocin X chain beta, and Plantaricin E/F was identified. These findings highlight the rich microbial diversity of homemade kimchi from Yibin and suggest that the HQ04 strain is a potential probiotic candidate for controlling pathogenic bacteria.